DISORDERS OF GASTROINTESTINAL TRACT FUNCTION IN INFANTS: THE PROBLEM AND THE ANALYSIS OF GENERALIZED DATA - N.I. Ursova ("Paediatrician" Publishers LLC, 2009)
The review analyzes the modern opinion on the problem of functional disorders of gastrointestinal tract, which are peculiar to infants. The peculiarities of nutrition and intestinal microbiocenosis in healthy infants are discussed. Authors observe the ways of its correction and propose the principles of a choice of medications, having proven clinical effectiveness in children on early stages of postnatal development. The advantages of natural smectite dioctaedric (Smecta) in prophylaxis and treatment of functional disorders of gastrointestinal system, acute and chronic diseases in children are presented. Key words: children of early age, gastrointestinal tract, function, nutrition, probiotics, smectite. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):48-54)